SERVER-SIDE PROCESSING TECHNIQUES FOR OPTIMIZING THE SPEED OF PRESENTING BIG DATA - Sulastri, Heni; Rahmatulloh, Alam; Hidayat, Deri Kurnia (LPPM Universitas Nusa Mandiri, 2019)
Big data is the latest industry keyword to describe large volumes of structured and unstructured data that are difficult to process and analyze. Most organizations are looking for the best approach to managing and analyzing large volumes of data, especially in decision making. Large data causes the process of presenting information to be slow because all the large amounts of data must be displayed so that specific techniques are needed so that the presentation of information remains fast even though the data is already large. The website generally processes requests to the server, and then if the required data is available, the server will send all the data. This causes all processes to be based on the client-side. So that the client load becomes heavy in displaying all the data. In this study, server-side processing techniques will be applied so that all processes will be handled by the server and the data sent is not all direct but based on periodic requests from the client. The results of this study indicate the use of server-side processing techniques is more optimal. Based on the results of testing the data presentation speed comparison with server-side processing techniques 98.6% is better than client-side processing.